The church in the early modern age - Dixon, C. Scott; Bloomsbury (Firm) (London, England : I.B. Tauris & Co. Ltd, 2016)
The years 1450-1650 were a momentous period for the development of Christianity. They witnessed the age of Reformation and Counter-Reformation: perhaps the most important era for the shaping of the faith since its foundation. C Scott Dixon explores how the ideas that went into the making of early modern Christianity re-oriented the Church to such an extent that they gave rise to new versions of the religion. He shows how the varieties and ambivalences of late medieval theology were now replaced by dogmatic certainties, where the institutions of Christian churches became more effective and 'modern', staffed by well-trained clergy. Tracing these changes from the fall of Constantinople to the end of the Thirty Years' War, and treating the High Renaissance and the Reformation as part of the same overall narrative, the author offers an integrated approach to widely different national, social and cultural histories. Moving beyond Protestant and Catholic conflicts, he contrasts Western Christianity with Eastern Orthodoxy, and examines the Church's response to fears of Ottoman domination.
Front cover; Half title ; Series list; Title ; Copyright ; Series Editor's Preface; Contents; Map 1; Map 2; Introduction; 1 -- Renaissance Christianity; 2 -- Reformation Christianity; 3 -- Religious Division; 4 -- Church and State; 5 -- Further Reform; 6 -- Christian Expansion; Conclusion; Notes; Further Reading; Index; Back cover.
Includes bibliographical references (pages 211-242) and index.
Also available in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web
Print version record.
Keywords: Church history -- 16th century; Church history -- 15th century; Church history -- 17th century; Electronic books